Evaluation of building energy efficiency investment options for the Kingdom of Saudi Arabia. (1st September 2017) - Krarti, Moncef; Dubey, Kankana; Howarth, Nicholas
Abstract: In this paper, economic and environmental impacts of energy efficiency programs associated with new and existing buildings are evaluated for the Kingdom of Saudi Arabia (KSA). In particular, the analysis considers optimized designs for new buildings as well as different energy retrofit programs for existing buildings are considered in the bottom-up analysis using archetypical building energy models located in five sites representing a wide range of KSA climates. In particular, the analysis presented in this paper provides specific estimations to the extent of the energy and demand savings that could be achieved in the building sector even under highly subsidized energy prices. It is found that even a basic energy retrofit program using low-cost energy efficiency measures implemented to the existing building stock can provide significant economic and environmental benefits. Indeed, a level 1 energy efficiency retrofit program targeting only the existing residential building stock could reduce electricity consumption by 10, 054 GWh/year and peak demand by 2290 MW and carbon emission by 7.611 million tons/year. Highlights: Benefits of energy efficiency programs for KSA new and existing buildings are evaluated. Optimization based analysis has been used in the analysis using a wide range of technologies. Significant benefits can incur form large scale building energy retrofit programs.